The Historicity of Health: Environmental Hazards and Epidemics in Northwest Greenland. (July 2019) - Hastrup, Kirsten
The Thule community (Northwest Greenland) sets the scene for this study of health and environmental hazards in a historical perspective. In the early 19th century, when European contact was first made, the region was still in the grip of the Little Ice Age, and the tiny population was on the brink of extinction partly owing to epidemics. This was to change in the late 19th century when more regular contact was made and provisions became more secure. During the 20th century, new political realities were mixed into the environmental issues, leaving the local population on the brink of disaster once again. Most recently, global warming is undermining the hunting economy, yet few subsistence alternatives are present this far in the High Arctic. Increasing contamination of the sea is having negative effects on all Arctic trophic levels with consequences for human health. This article discusses the historicity of health, and the unification of the world through disease and pollution and unpacks a pervasive sense of disequilibrium owing to many factors.